Hubungan Hukum Adat sebagai Living Law pada Proses Acara Peradilan Pidana Penyandang Disabilitas - St.Puan Khaliza A. iIham; Audyna Mayasari Muin; Maskun Maskun; Iin Karita Sakharina (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Integration of customary law as living law in the judicial process for persons with disabilities. Customary law, a dynamic concept, has the potential to enrich the principles of restorative justice and reasonable accommodation as stipulated in Law Number 20 of 2025 concerning the Criminal Procedure Code. This study analyses the relationship between customary law as a living law and criminal procedure mechanisms, including customary deliberations for restorative justice for victims and defendants with disabilities, as well as reasonable accommodations. The findings demonstrate the need for formal recognition of customary law in Supreme Court Regulations (Perma/Regulations) to achieve inclusive justice for persons with disabilities.